Evaluation of physico-chemical factors influence on corrosion activity of water - Тамазашвілі, Анжела Тамазівна; Мазна, Юлія Ігорівна; Малихіна, Каріна Артурівна; Гомеля, Микола Дмитрович (Eastern-European Journal of Enterprise Technologies, 2013)
The paper investigated corrosion processes and determined the level of various aqueous media activity towards metals. Corrosion rate was determined by a manometric method and polarization resistance method. Tap water, artesian water and standard test solution were used as media of comparisons. The influence of pH, temperature and salinity on the rate of metals corrosion was defined. It was found that corrosion activity of neutral aqueous medium depends on the concentration of dissolved oxygen and the content of salt anions in water. It was proved that dissolved inorganic salts significantly accelerate corrosion process. It was found that at the temperature of 20 ºC, with decreased oxygen concentration in static conditions, corrosion rate decreases. It was shown that at high temperatures, the initial concentration of oxygen as well as pH medium, have little effect on corrosion activity of water, since in this case, corrosion of steel is mainly determined by chemical interaction of metal with water.